Rainbow over SGS - Hauser, C. Sean, photographer (Colorado State University. Libraries, 2006)
Panoramic view of both ends of rainbow from SGS LTER HQ, using NRELSGSL100154 and NRELSGSL100155.
Keywords: grasslands; SGS; rainbow; landscapes